2018
DOI: 10.1073/pnas.1804876115
|View full text |Cite
|
Sign up to set email alerts
|

Subspecialization within default mode nodes characterized in 10,000 UK Biobank participants

Abstract: SignificanceThe default mode network (DMN) encompasses supramodal association areas involved in higher-order cognition. One speculation is that this neural system is important for brain-wide information flow. We tested this account by exploring whether DMN patterns are informative about functional coupling or structural associations in the rest of the brain. Our multimodal pattern analysis findings highlight how the DMN nodes are fractionated: In specific subnodes, gray-matter morphology was linked to fiber tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 48 publications
3
132
1
1
Order By: Relevance
“…Recent advances in mapping the human cortex have discovered a clear gradient of structural and functional features that spans across the sensory-motoric system and the multimodal system, found in both humans and non-human primates (10,12,13,(43)(44)(45). An evident neurocognitive dimension of 'internal vs. external preference' underlies this cortical gradienton one extreme of the spectrum, the cortical regions are highly modality-specific (e.g., the primary visual/auditory cortex; 10), respond to external events occurring here and now (i.e., showing narrow spatiotemporal receptive fields; 46), and prefers concrete, perceivable stimuli to abstracted, conceptual stimuli (47).…”
Section: Large-scale Gradational Structure Of the Human Cortexmentioning
confidence: 99%
“…Recent advances in mapping the human cortex have discovered a clear gradient of structural and functional features that spans across the sensory-motoric system and the multimodal system, found in both humans and non-human primates (10,12,13,(43)(44)(45). An evident neurocognitive dimension of 'internal vs. external preference' underlies this cortical gradienton one extreme of the spectrum, the cortical regions are highly modality-specific (e.g., the primary visual/auditory cortex; 10), respond to external events occurring here and now (i.e., showing narrow spatiotemporal receptive fields; 46), and prefers concrete, perceivable stimuli to abstracted, conceptual stimuli (47).…”
Section: Large-scale Gradational Structure Of the Human Cortexmentioning
confidence: 99%
“…Yet, the PMC is often treated as having a homogenous functional architecture in studies of the DMN, despite its diverse patterns of functional connectivity (Y. Zhang et al, ). Recent work characterising the functional architecture of the PMC has shown that it consists of several different functional subdivisions that are associated with multiple large‐scale brain networks at rest (Kernbach et al, ; Leech, Braga, & Sharp, ; S. Zhang & Li, ). In particular, the posterior cingulate cortex (PCC), which lies in the medial part of the inferior parietal lobe, exhibits distinct cytoarchitectonics with functional separation into dorsal and ventral areas (Leech, Kamourieh, Beckmann, & Sharp, ; Vogt, Vogt, & Laureys, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, 2014). Recent work characterising the functional architecture of the PMC has shown that it consists of several different functional subdivisions that are associated with multiple large-scale brain networks at rest (Kernbach et al, 2018;Leech, Braga, & Sharp, 2012;S. Zhang & Li, 2012).…”
mentioning
confidence: 99%
“…Both sub-systems might spatially overlap or inter-digitate across multiple brain regions (Andrews-Hanna et al, 2014;Rodrigo and Buckner, 2017), which would be challenging to ALE without assuming prior knowledge of the sub-systems ( Figure 1). Furthermore, specific default network fractionation details differed across studies Mayer et al 2010;Humphreys et al, 2015;Kernbach et al, 2018), so application of the author-topic model might potentially clarify sub-systems subserving self-generated thought.…”
Section: Discovering Sub-domains Of Self-generated Thoughtsmentioning
confidence: 99%